Does pre‐exercise static stretching inhibit maximal muscular performance? A meta‐analytical review. Issue 2 (8th February 2012) - Simic, L.; Sarabon, N.; Markovic, G.
Abstract : We applied a meta‐analytical approach to derive a robust estimate of the acute effects of pre‐exercise static stretching (SS) on strength, power, and explosive muscular performance. A computerized search of articles published between 1966 and December 2010 was performed using PubMed, SCOPUS, and Web of Science databases. A total of 104 studies yielding 61 data points for strength, 12 data points for power, and 57 data points for explosive performance met our inclusion criteria. The pooled estimate of the acute effects of SS on strength, power, and explosive performance, expressed in standardized units as well as in percentages, were −0.10 [95% confidence interval (CI): −0.15 to −0.04], −0.04 (95% CI: −0.16 to 0.08), and −0.03 (95% CI: −0.07 to 0.01), or −5.4% (95% CI: −6.6% to −4.2%), −1.9% (95% CI: −4.0% to 0.2%), and −2.0% (95% CI: −2.8% to −1.3%). These effects were not related to subject's age, gender, or fitness level; however, they were more pronounced in isometric vs dynamic tests, and were related to the total duration of stretch, with the smallest negative acute effects being observed with stretch duration of ≤45 s. We conclude that the usage of SS as the sole activity during warm‐up routine should generally be avoided.